Ekonomi Islam: transaksi dan problematikanya - Muhammad Anton Athoillah (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
Transaction in Islam is often criticized for not having a clear differentiator from the other transaction. Although departing from the different basic principles, but havingnot a much different impact than the other transaction. Often asked, whether Islamic economics is capitalism minus usury or socialism plusIslam? Therefore, no less important to know are, what a plus-minus of conventional transaction, what the distinguishing element between a conventional transaction with Shari’ah transaction, and whether the distinguishing element has different impact than what is produced by a conventional transaction.